Pengaruh Biaya Bahan Baku dan Tenaga Kerja Terhadap Biaya Produksi Pabrik Tempe Ramli Medan - Yessi Novitasari Laia; Sartika Sartika; Josua Bima Panjaitan; Aurora Elise Putriku (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of raw material costs and labor costs on production costs at Tempe Ramli Factory in Medan. Raw material and labor costs are two essential components in the production process that significantly influence overall cost efficiency and effectiveness. This research employs a quantitative approach using multiple linear regression analysis. The population in this study includes all employees of the Tempe Ramli Factory, with a total sample of 30 respondents selected using a saturated sampling technique. Data were collected through observation, questionnaires, and documentation, and analyzed using SPSS software. The results indicate that both raw material costs and labor costs have a positive and significant effect on production costs, both partially and simultaneously. Among the two, raw material costs are the most dominant factor affecting production costs. These findings highlight the importance of efficient management of raw material and labor costs to optimize production expenditures.